Thrombophilia in young adults with ischemic stroke: an overview - Mineikytė , R.; Kryžauskaitė , L.; Ryliškienė , K. (Neurologijos seminarai, 2019)
Thrombophilia broadly defines inherited or acquired coagulation disorders associated with increased tendency to form intravascular thrombi. Evaluation for thrombophilia in young patients with cryptogenic stroke is a frequent clinical question. Although the prevalence of this disorder is low in stroke patients, identification of it may influence secondary prevention strategy. No validated testing and secondary prevention with anticoagulation guidelines have been published. The aim of the article is to provide an update overview on the leading thrombophilic factors and their epidemiological and clinical association with stroke.
Keywords: thrombophilia; hereditary; acquired; arterial; venous; young stroke patients